Sleep is atypical across neurodevelopmental disorders in infants and toddlers: A cross-syndrome study - D'Souza, D; D'Souza, H; Horváth, K; Plunkett, K; Karmiloff-Smith, A (Elsevier, 2019)
This cross-syndrome study focuses on sleep and its relationship with language development. Children with neurodevelopmental disorders present with language delay. Typical language development is constrained by numerous factors including sleep. Sleep is often disrupted in adolescents/adults with neurodevelopmental disorders. We therefore hypothesised that sleep may be disrupted, and correlate with language development, in infants/toddlers with neurodevelopmental disorders. To test our hypothesis, we obtained sleep and vocabulary size data from 75 infants/toddlers with one of three neurodevelopmental disorders (Down syndrome [DS], fragile X syndrome [FXS], Williams syndrome [WS]). Sleep was indeed disrupted in these children. It was also positively associated with receptive vocabulary size in the infants/toddlers with DS and WS (we could not test the relationship between sleep and language in FXS due to lack of power). We argue that disrupted sleep may be a common occurrence in very young children with neurodevelopmental disorders, and it may relate to their ability to acquire their first language.